Doktrin Bush: Satu analisis hegemoni berideologi gramsci - Muhamad Takiyuddin Ismail, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
The Bush Doctrine, identified with the document “The National Security Strategy of the United States” (2002) was articulated after the attack of 11th September 2001, or more commonly known as “9/11”. The two main pillars of the doctrine - preemptive attack and regime change - has been the subject of much debate on the pattern of foreign policy under the Bush administration. Since a major objective of the doctrine as generally perceived by scholars was to secure US hegemony in international politics, it is thus imperative to analyse the relationship between the Bush Doctrine and the ideological hegemony theory, as introduced by the Italian Marxist thinker, Antonio Gramsci (1891-1937). The analysis will demonstrate that the Bush Doctrine seems to have failed to meet its objective, and on the contrary, has experienced a strong counter-hegemony due to the growing chaos and anarchy in the Iraq War